1986
DOI: 10.1016/0014-5793(86)81078-x
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence decay kinetics in relation to the relaxation of the transthylakoid ΔpH from high and low CO2 adapted cells of Scenedesmus obliquus

Abstract: Luminescence decay kinetics was shown to be. polyphasic with two relative maxima observed, when high CO, adapted cells of Scenedesmus obliquus were stressed by CO, deficiency. Low CO, adapted cells exhibited a single maximum. Luminescence from high CO, adapted cells under high CO, conditions decayed asymptotically without maxima. The magnitude of the transthylakoid dpH was shown to be. related to the intensity of luminescence in an antiparallel way. The relaxation kinetics of the dpH was shown to be complex, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…As a consequence, reoxidation of PQ may well proceed at a high rate even though the rate of energy turnover through PSII has decreased (14). Taken together, our results support the idea that increased cyclic electron transport around PSI may provide the cells with extra ATP for the CCM (24,26,29), but apparently at the cost of a decreased noncyclic electron transport (Fig. 6).…”
Section: Low-ci-induced Changes Of Fluorescence Quenchingsupporting
confidence: 79%
See 1 more Smart Citation
“…As a consequence, reoxidation of PQ may well proceed at a high rate even though the rate of energy turnover through PSII has decreased (14). Taken together, our results support the idea that increased cyclic electron transport around PSI may provide the cells with extra ATP for the CCM (24,26,29), but apparently at the cost of a decreased noncyclic electron transport (Fig. 6).…”
Section: Low-ci-induced Changes Of Fluorescence Quenchingsupporting
confidence: 79%
“…Several studies have dealt with changes in photosynthetic C02-response characteristics and changes in carbonic anhydrase levels that occur when algae are transferred from high to low Ci concentrations (2-4, 13, 17, 22, 23). However, there are few studies dealing with the regulation of the photosynthetic energy transducing reactions (24,26,29) …”
mentioning
confidence: 99%
“…In Sundblad et al (1986b) the luminescence maximum from low CO2 adapted Scenedesmus was shown to be correlated to a rapid relaxation of nonphotochemical quenching of maximal fluorescence. It was concluded that the luminescence maximum appeared as a result of a rapid energetic turnover in low CO2 adapted cells and that the luminescence maximum and the rapid relaxation of nonphotochemical quenching reflected a rapid ApH relaxation.…”
Section: Resultsmentioning
confidence: 99%
“…An I AG /I B ratio of 1.17 has been determined in L. japonicus plants grown under air conditions (Table ). As already mentioned, the intensity of AG emission is considered as an in vivo indicator of the assimilatory potential (NADPH + ATP) when it is inducible by a white light illumination in green algae (Mellvig and Tillberg , Palmqvist et al , Sundblad et al ) or flash excitation in plants (Miranda and Ducruet , Krieger et al ). The assimilatory potential, which is also dependent on the cellular energetic status, has also been correlated to the dihydroxyacetone‐P/PGA ratio (Heber et al ).…”
Section: Discussionmentioning
confidence: 99%